2007
DOI: 10.1085/jgp.200709800
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Determinants of PI(4,5)P2 and PI(3,4,5)P3 Regulation of the Epithelial Na+ Channel

Abstract: Phosphatidylinositol 4,5-bisphosphate (PI(4,5)P2) and phosphatidylinositol 3,4,5-trisphosphate (PI(3,4,5)P3) are physiologically important second messengers. These molecules bind effector proteins to modulate activity. Several types of ion channels, including the epithelial Na+ channel (ENaC), are phosphoinositide effectors capable of directly interacting with these signaling molecules. Little, however, is known of the regions within ENaC and other ion channels important to phosphoinositide binding and modulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
94
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
4
1

Relationship

2
8

Authors

Journals

citations
Cited by 73 publications
(103 citation statements)
references
References 78 publications
(139 reference statements)
8
94
0
Order By: Relevance
“…Recent studies indicate that ENaC activity can be increased directly by phosphatidylinositides (35,37). In the present study, we revealed the importance of PI4-kinases in the taste system.…”
Section: Discussionsupporting
confidence: 63%
“…Recent studies indicate that ENaC activity can be increased directly by phosphatidylinositides (35,37). In the present study, we revealed the importance of PI4-kinases in the taste system.…”
Section: Discussionsupporting
confidence: 63%
“…In addition to ROMK1, ENaC is also regulated by cholesterol 34,35 and PI(4,5)P 2 . [36][37][38] However, unlike ROMK1 channels, ENaC appears to be localized in microvilli. 39 Therefore, investigating how cholesterol and PI(4,5)P 2 regulate ENaC in microvilli would serve as interesting topics for our future studies.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, however, PI(3,4,5)P 3 was shown to regulate TRPC6 by disrupting its association with calmodulin (11), and PI(4,5)P 2 has been reported to be important for ENaC channel gating and PI(3,4,5)P 3 for ENaC channel open probability and number (9,10). These results suggest that different phosphoinositides in a cell can regulate different functional aspects of the same protein.…”
Section: Discussionmentioning
confidence: 99%